Patai's Chemistry of Functional Groups 2014
DOI: 10.1002/9780470682531.pat0704
|View full text |Cite
|
Sign up to set email alerts
|

Positively Charged Selenium‐ and Tellurium‐Stabilized Species

Abstract: Cationic chalcogenium species have attracted some attention due to the ability of these highly electropositive centers to interact with organic molecules or to provide strong π‐accepter ligands for transition metals. Though the cationic selenium and tellurium species are very useful for organic synthesis, most of the naked cationic chalcogen species, with the exception of tricoordinated chalcogenium salt (R 3 Ch + , Ch = chalcogen atoms), are unstable and difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The pioneering studies conducted by Ragogna et al , since 2006, have reported the tridentate-, 71 N-heterocyclic bidentate, 71–74 and bis-monodentate 75 chalcogen( ii ) dications. 76 However, these bis- or tri-coordinate species exhibit a double lone pair of electrons without vacant orbitals, leading to distinct electron configurations and reactivity compared to the group 13–15 analogues. Herein, further discussion regarding group 16 analogues will not be pursued in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering studies conducted by Ragogna et al , since 2006, have reported the tridentate-, 71 N-heterocyclic bidentate, 71–74 and bis-monodentate 75 chalcogen( ii ) dications. 76 However, these bis- or tri-coordinate species exhibit a double lone pair of electrons without vacant orbitals, leading to distinct electron configurations and reactivity compared to the group 13–15 analogues. Herein, further discussion regarding group 16 analogues will not be pursued in this review.…”
Section: Introductionmentioning
confidence: 99%